PENGARUH MODEL INQUIRY LEARNING BERBANTUAN MEDIA EDUCAPLAY TERHADAP HASIL BELAJAR KOGNITIF KOMPONEN PETA PADA SISWA KELAS IV SD - Sania Ramadhani; Sofyan Iskandar; Tiara Yogiarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The background of this study stems from the issue of low student learningoutcomes, which are attributed to a lack of active engagement in the learningprocess and the suboptimal use of instructional media. This study aims to examinethe effect of the Inquiry Learning model assisted by Educaplay media on students’cognitive learning outcomes in the topic of Map Components for fourth-gradeelementary students. The method used is a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. Theresearch subjects consisted of two classes: the experimental class, whichimplemented the Guided Inquiry model assisted by Educaplay, and the controlclass, which used the Modified Free Inquiry model. The research instrument was acognitive learning outcome test in the form of 20 multiple-choice questions. Thedata analysis results showed that the Inquiry Learning model assisted byEducaplay led to a 66% improvement in students’ cognitive learning outcomes,categorized as moderately effective. Meanwhile, the class using the Modified FreeInquiry model showed a 42% improvement, which falls into the less effectivecategory. Therefore, it can be concluded that the Inquiry Learning model assistedby Educaplay has a positive effect on improving elementary school students’cognitive learning outcomes, with a difference in improvement of 18.4%.